Permeability of Broken Coal Around CBM Drainage Boreholes with the Compound Disaster of the Rockburst and Outburst - Lei Zhang; Shihua Yang; Hongyu Pan; Tianjun Zhang (Applied Sciences)
Coal seam gas drainage serves as an effective engineering measure to mitigate compound disasters of the rockburst and outburst in deep mining, and its efficacy is fundamentally governed by the permeability of coal around the gas drainage borehole. To systematically study the permeability law of broken coal body around borehole under different stress states and particle size distribution, the coal particle samples were prepared for the triaxial permeability tests by the gradation theory whose Talbot power exponents n are 0.1 to 1.0. Several valuable findings have been obtained through meticulous research and analysis, according to Darcy’s law and the Forchheimer equation. The seepage velocity is affected by the Talbot power exponent, pressure gradient, confining pressure, and axial pressure, among which the pressure gradient has the most prominent influence. The larger the Talbot power exponent of the sample composition and the larger of the pressure gradient inside the sample, the larger is the seepage velocity obtained by the sample. The axial pressure has a notable influence on permeability by modifying the pore structure of broken coal. As the axial pressure increases, the permeability decays exponentially until it reaches a stable state at a specific limit. The permeability decreases exponentially with the increase of effective stress, while the power exponent (a) decreases gradually with the increase of Talbot power exponent, and the coefficient (b) increases gradually with the increase of Talbot power exponent (index), in the effective stress-permeability equation, which implies that the inhibition and amplitude effects of effective stress on permeability become more intense. The permeability shows three stages of growth, namely the slow growth stage, the linear growth stage, and the exponential growth stage, which are influenced by small-sized coal particles, particle-size ratio, and large-sized coal particles respectively, when the Talbot power exponent (n) of the broken coal increases from 0.1 to 1.0. These findings advance understanding of the permeability of broken coal around boreholes, providing theoretical foundations for optimizing gas drainage parameters and preventing the compound disaster of the rockburst and outburst.